Isolation and Structure Elucidation of Cyclohexanepentol, an Anti-Psychotic Agent from Cissampelos owarensis (P. Beauv.) Leaves (Nigerian Journal of Pharmaceutical Research, 2023)
Background: In Nigeria, an estimated 20 – 30% of our population is believed to suffer from mental disorders. Cissampelos owariensis has been used in Southwest Nigerian traditional medicine to treat mental illness.Objectives: This study evaluated the anti-psychotic potential of Cissampelos owariensis crude extract, fractions, sub-fractions and isolated compound, using in vivo and in vitro antipsychotic assays.Material and Methods: Crude extract and fractions of the leaves were investigated against ketamine induced hyper-locomotion and stereotype behaviours in mice. Extrapyramidal effect of bioactive fraction was tested using catalepsy model. D - amino acid oxidase assay was used to test for anti-psychotic property of chromatographic sub-fractions and isolated compound. Percentage inhibition of pooled sub-fractions and compound was measured at an excitation and emission wavelengths of 355 and 460 nm, respectively. Characterization of isolated compound was done using Infrared and Nuclear Magnetic Resonance spectroscopy. One-way ANOVA, followed by Dunnett’s posthoc test at α0.05, was used for data analysis.Results: Crude extract of Cissampelos owariensis (125 mg/kg) and fractions showed reduction in hyper-locomotion at different doses. The extract (125 mg/kg) and ethylacetate fraction (500 mg/kg) significantly antagonized stereotypy in mice. The ethyl acetate fraction did not induce catalepsy but rather reversed the cataleptic effect induced by haloperidol. Phytochemical investigation led to the identification of Cyclohexanepentol, which possesses comparable anti-psychotic activity with Risperidone.Conclusion: This paper presents for the first time, anti-psychotic principle from C. owariensis and validates its ethno-medicinal use.
Keywords: Cissampelos owariensis; Cyclohexanepentol; Antipsychotic agent; D-amino acid oxidase; Chromatography